PEMANFAATAN LIMBAH MINYAK JELANTAH MENJADI LILIN AROMATERAPI UNTUK MENINGKATKAN EKONOMI LOKAL DESA PURWODADI - putra, joni; -, Mahasiswa KKN Univeristas Lampung (BUGUH: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
Community Service (KKN) is a mandatory program for students of the Faculty of Teacher Training and Education that aims to empower rural communities through the application of science. In 2025, students from the University of Lampung will carry out KKN in Purwodadi Village, Trimurjo District, Central Lampung Regency, focusing on managing used cooking oil waste into aromatherapy candles. Used cooking oil, as household waste, has the potential to pollute the environment if not managed properly. This program involves training in the aromatherapy candle production process, starting from clarifying used cooking oil, mixing ingredients such as palm wax and essential oils, to the molding and cooling stages. This candle product not only provides a relaxing effect, but also becomes an economical business opportunity. This activity aims to reduce waste, increase public awareness of the importance of recycling, and create new business opportunities to support the local economy. The results of this program are expected to have a positive impact on the environment, socially, and economically for the people of Purwodadi Village.